The Blue-Blood Porcine Chest Wall: A Novel Microsurgery Training Simulator for Internal Mammary Vessel Dissection and Anastomosis - Zeng, Weifeng; Gunderson, Kirsten A.; Sanchez, Ruston J.; Albano, Nicholas J.; Nkana, Zeeda H.; Thadikonda, Kishan M.; Dingle, Aaron M.; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2020)
Background Preparation of the internal mammary artery (IMA) is a critical step in autologous breast reconstruction. Intraoperatively, there is limited opportunity for residents to practice this skill. Porcine models provide highly realistic simulation for vascular surgery; however, use of live laboratory pigs is expensive, inconvenient, and offers limited opportunity for repetitive training. We aimed to develop an inexpensive and effective training model for IMA preparation. This article describes creation of a novel microsurgical model using cadaveric chest walls of Wisconsin Miniature Swine embedded in a modified mannequin thorax and augmented with a blue-blood perfusion system.Methods Anatomic comparison: five porcine chest walls were dissected, and various anatomic measurements were made for anatomic comparison to existing human data in the literature. Model assembly: the chest wall is prepared by cannulating the proximal and distal ends of the internal mammary vessels with angiocatheters, which are then connected to the blue-blood perfusion system. The model is assembled in four layers including: (1) a mannequin thorax with a window removed to expose the first to fourth intercostal spaces, bilaterally, (2) a layer of foam simulating fat, (3) the perfused pig chest wall, and (4) a second mannequin shell placed posteriorly for support.Results The porcine chest walls are similar to humans with regards to vessel size and location. This model can be assembled quickly, with a one-time approximate cost of $55.00, and allows for six training sessions per specimen. The model allows residents to practice the key steps of IMA preparation including dissection, elevation of perichondria, and vascular anastomosis while working at a depth that closely simulates the human thorax. Continuous blue-blood perfusion provides immediate feedback on anastomosis quality.Conclusion Overall, this novel model can provide inexpensive and realistic simulation of internal mammary vessel preparation and anastomosis.
Keywords: surgical simulation; surgery education; pig model